Improved design of a Wells turbine for higher operating range. (June 2017) - Halder, Paresh; Samad, Abdus; Thévenin, Dominique
Abstract: The oscillating water column (OWC), which is a wave energy extracting device, uses a bidirectional flow turbine to generate power. The device performance largely depends on the efficiency, torque and operating range of the turbine. The turbine with a larger operating range produces power during a wider wave height and period, both properties changing throughout the year or during each wave cycle. In this article, a numerical work relying on design optimization is reported to show the dependency of power extraction capability to the operating range of the turbine. Reynolds-averaged Navier-Stokes (RANS) equations were solved and a surrogate approximation model was constructed to find an optimal design. Design variables were blade sweep angles at the tip and mid sections. The objective function, to be maximized, is the torque coefficient. The optimal design delayed the flow separation and the peak efficiency dropped by 3.1%. At the same time, the relative power output and the relative stall point were increased by 29% and 18% compared to the reference case, respectively. Highlights: Numerical optimization via CFD has been explained. The relative power output of a Wells turbine up to 31% and stall delayed by 18% by modifying design parameters. An optimization approach using Kriging based low fidelity model has been implemented.